Fast iterative pre‐emphasis calibration method enabling third‐order dynamic shim updated fMRI. Issue 3 (7th May 2015) - Fillmer, Ariane; Vannesjo, Signe Johanna; Pavan, Matteo; Scheidegger, Milan; Pruessmann, Klaas Paul; Henning, Anke
Abstract : Purpose: To calibrate a pre‐emphasis to sufficiently compensate eddy currents for application of dynamic shim updating to fMRI without extension of scan times. Methods: Eddy current effects induced into all shim terms up to third‐order were characterized by spatiotemporal field monitoring, using a third‐order field camera. Pre‐emphasis settings were derived from the measurements and iteratively evaluated and refined. The calibrated pre‐emphasis was applied to slice‐wise dynamic shim updating in combination with a dynamic excitation frequency (F0) determination and a slice‐wise B 0 optimization routine for in vivo echo planar imaging and resting‐state functional MRI. Results: The described method for pre‐emphasis calibration led to settling times of remaining eddy current effects below 2 ms, allowing for the application of dynamic shim updating to fMRI without extension of scan times or induction of eddy current related artifacts. A dynamic F0 determination compensates frequency shifts induced by the superposition of different shim fields, and therefore, prevents an image shift within the field of view. Hardware limitations necessitate the reduction of the maximum applicable B 0 shim field amplitudes and restrict the shim performance. Conclusion: The proposed method enables accurate pre‐emphasis calibration, and therefore, the application of dynamic shim updating to fMRI. Magn Reson Med 75:1119–1131, 2016. © 2015 Wiley Periodicals, Inc.